A community for students.
Here's the question you clicked on:
← 55 members online
 0 viewing
smurfy14
 5 years ago
did i get the right answer? (file attached)
smurfy14
 5 years ago
did i get the right answer? (file attached)

This Question is Closed

myininaya
 5 years ago
Best ResponseYou've already chosen the best response.0hey smurfy f(x+h)f(x)=[(x+h)^31][x^31] =x^3+3x^2h+3xh^2+h^31x^3+1 =3x^2h+3xh^2 =3xh(x+h) (but h=x+3) so =3x(x+3)(x+(x+3)) =3x(x+3)(2x+3)

myininaya
 5 years ago
Best ResponseYou've already chosen the best response.0=3x(2x^2+3x+6x+9) =3x(2x^2+9x+9) =6x^3+27x^2+27x

smurfy14
 5 years ago
Best ResponseYou've already chosen the best response.0oh ok thanks myininaya :)
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.